Transformation of the Business Model for Palm Sugar Enterprises Based on Collective Institutions: A Business Model Canvas Approach in Labuaja Village - Makkarennu; Syahidah; Supratman; Dian Ayu Lestari Hasannudin; Soni Trison; Adelia Caroline; Irnasari (Jurnal Hutan dan Masyarakat, 2026)
Sugar palm (Arenga pinnata) is one of the non-timber forest products widely utilized by rural communities to support their livelihoods. However, community-based palm sugar enterprises often face limitations in management practices, value addition, and market access. This study aims to identify and analyze the management of palm sugar businesses, examine the existing business models, and formulate strategies for business model transformation. The study was conducted in Labuaja Village, Maros Regency, involving 20 members of a forest farmer group actively engaged in palm sugar production. Data were collected through field observations and interviews, focusing on raw material preparation, production processes, post-harvest handling, and packaging practices. The results show that palm sugar enterprises are still managed using simple and traditional methods, with a single-product orientation and limited product diversification. Consequently, value addition remains low, and marketing constraints hinder business development. To address these challenges, this study proposes the integration of institutional-based marketing strategies into the Business Model Canvas as an approach to support adaptive and sustainable business transformation. Strengthening local institutions, promoting product diversification, and expanding market access are identified as key strategies to enhance the competitiveness of community-based palm sugar enterprises.